Saariselän matkailualan yritysten sesonkityöntekijöiden asumiseen liittyvät ratkaisumallit - Alariesto, Susanna; Antola, Janne (2023)
The purpose of the functional thesis is to find out the needs related to the accommodation of seasonal employees of tourism companies operating in Saariselkä, and to map out what kind of means the companies can use to get more beds. The goal is to find development measures that enable tourism companies operating in Saariselkä to get more beds for their seasonal employees. Beds provided by companies increase employee satisfaction, improve retention and attractiveness, and facilitate recruitment. The supervisor of the thesis is Inari Municipality. The research question is to find out the needs and capabilities related to accommodation solutions of seasonal employees of tourism companies. As a sub-question, we will find out what kind of accommodation solutions can be used to increase the beds for seasonal workers of tourism companies operating in Saariselkä, and what kind of housing solutions the companies hope for, in order to improve the attraction and retention power among seasonal workers. In the theory section, the development of the municipality of Inari and the housing situation, tourism in Lapland and seasonal work in tourism, housing for seasonal workers, recruitment and the effect of employer image on attraction and retention were discussed. The thesis was done by means of action research and it used both quantitative and qualitative research methods. A qualitative survey was conducted for companies in the tourism industry in Saariselkä and its surrounding areas. In the functional part, the Saariselkä housing solutions event was organized. As a result of the thesis, development proposals were created, with the help of which it is possible to improve the housing situation of Saariselkä seasonal employees. The development proposals are enabling alternative accommodation solutions, improving the availability and price of plots, and communicating the housing shortage. The results can be used as help in other tourist centers that require accommodation for seasonal workers. Toiminnallisen opinnäytetyön ...